Probing chemical environment with molecular double core-hole electron spectroscopy - Takahashi, Osamu; Kryzhevoi, Nikolai V.; Ueda, Kiyoshi (Journal of electron spectroscopy and related phenomena, 2015)
With the advent of X-ray free electron lasers and the development of elaborate multi-coincidence methods combined with conventional synchrotron radiation, the interest in double core-hole spectroscopy revived. To describe the measured data and provide the guideline for yet coming experiments, theoretical studies are required. In this paper we review previous theoretical works on double core-hole states and discuss new theoretical results for the XHm-YHn (X, Y=C, N, O, or F; m,n=0-3) molecules and their fluorine substituted compounds. We compute the single and double core-hole binding energies of these systems using different methods and show that the DFT results agree well with the results of other ab initio methods. In agreement with previous theoretical works, our study demonstrates that the changes in the ionization potential resulting from fluorine substitutions mainly arise due to changes in the ground state and not due to electron relaxation. Special emphasis is given to interatomic relaxation originating from creation of two core holes on different atomic sites. We demonstrate that there exists clear correlation between this quantity, the number of hydrogen atoms and the order of the bond between the heavy atoms in the systems studied.
Gesehen am 25.06.2020